Berberine Influences the Survival of Fat Grafting by Inhibiting Autophagy and Apoptosis of Human Adipose Derived Mesenchymal Stem Cells - Pang H; Zhou Y; Wang J; Wu H; Liu X; Gao F; Xiao Z (Dove Medical Press, 2021)
Hao Pang, Yongting Zhou, Jie Wang, Hao Wu, Xueyi Liu, Feng Gao, Zhibo Xiao Department of Plastic Surgery, The Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150086, People's Republic of ChinaCorrespondence: Zhibo XiaoDepartment of Plastic Surgery, The Second Affiliated Hospital of Harbin Medical University, No. 246 Xuefu Avenue, Harbin, Heilongjiang, 150086, People's Republic of ChinaEmail xiaozhibodoctor@126.comObjective: Human adipose-derived mesenchymal stem cells (ADSCs) have the potential to be applied to solid organ treatments. However, tissue regeneration is limited by the death of transplanted cells. Ischemia is the main cause of the poor outcome. This study aimed to investigate the effect of berberine (BBR) on ADSCs after fat grafting.Methods: The antioxidant BBR on apoptosis and autophagy of ADSCs in vitro ischemia model was induced by hypoxia and serum deprivation (HY/SD). The autophagy promoter rapamycin and autophagy inhibitor 3-MA were incubated separately to investigate the crosstalk between autophagy and apoptosis. Pathway inhibitors further verified whether the autophagy and apoptosis were regulated by AMPK/mTor signaling pathway. Fat survival, fibrosis, level of inflammatory cell infiltration, and the effect of angiogenesis after BBR treatment were observed in vivo.Results: BBR could reduce ROS production and reverse the decreasing cell survival rate. HY/SD would induce apoptosis and autophagy in ADSCs, and BBR could alleviate these processes. After interfering with the level of autophagy, we also proved that apoptosis was regulated by autophagy and changed accordingly. The results also indicated that BBR could protect against autophagy and apoptosis of ADSCs through AMPK/mTor pathway. The treated human-derived adipose tissue was transplanted into BALB/c nude mice, and with the intervention of BBR, the fat grafting had a higher survival rate, lower inflammatory cell infiltration and fibrosis level.Conclusion: Our present study revealed that BBR was a promising anti-autophagy and apoptosis agent for improving the survival rate of ADSCs during cell transplantation.Keywords: adipose derived mesenchymal stem cells, berberine, autophagy, apoptosis, fat grafting